REVIEWING THE IDEA OF ISLAMIC ETHICAL PARADIGM OF PROPHETIC SCIENCE THINKING KUNTOWIJOYO - Arditya Prayogi (Al-Nizam: Indonesian Journal of Research and Community Service, 2023)
This article aims to review the views of an Indonesian Muslim scholar, Kuntowijoyo, in viewing the position of science in an ethical paradigm, both theoretical and practical. This is motivated by an ethical approach to science (knowledge) which departs from a belief that basically nothing is truly neutral or value-free; science is full of biases and the interests of its formulators. This article was written using a descriptive-qualitative approach supported by a data collection method in the form of a literature study. From the discussion it is known that ethically Kuntowijoyo sees the basis of knowledge as value-free standing. Theoretically, according to Kuntowijoyo, there are four aspects that are relevant to discuss, namely the ultimate goal of the Islamic paradigm, the involvement of the Islamic paradigm in history, methodological objectivism, and attitudes towards secular sciences. In practice, the ethical paradigm of prophetic science can be realized in three ways, including theorizing, structuring, and transformation.